Shaoyao Gancao decoction alleviates paclitaxel-induced cognitive impairment by activating PTEN/PI3K/AKT pathway to inhibit NETs formation - Xu Ying; Su Yue; Hu Yuwen; Li Xiang; Zhou Ziyan; Yuan Ningning; Ji Xiaowei; Jiang Ruoyu; Wang Wenzhu; Zhang Yafeng; Zhai Guojie; Cheng Xiaolan (Phytomedicine Plus)
Purpose: Paclitaxel-induced cognitive impairment (PICI) is a frequent and severe adverse reaction of chemotherapy. Increased neuroinflammation related to neutrophil extracellular traps (NETs) may play a key role in PICI. Shaoyao Gancao Decoction (SGD) is a classic Chinese prescription with good neuroprotective activities. However, the action of SGD in PICI remains elusive. Herein, our work was set out to study the potential role and possible mechanism of SGD in PICI through network pharmacology, Mendelian analysis and animal experiments. Methods: First, network pharmacology analysis was performed to identify the potential active compounds and targets of SGD on PICI. Secondly, PICI mice model was established, and the neuroprotective effects of SGD on PICI mice were eveluated by using new object recognition, Morris water maze test and TUNEL staining. The impact of SGD on inflammatory factors, microglia activation and NETs formation were also studied by ELISA and immunofluorescence. The regulation of SGD on PTEN/PI3K/AKT pathway was detected by Western blot. Finally, Mendelian randomization was performed using genome-wide association analysis data of PTEN and cognitive disorders in OpenGWAS database. Results: Network pharmacological analysis revealed 105 active ingredients in SGD, and identified 124 targets associated with SGD and PICI. KEGG pathway analysis implied that PI3K-AKT signaling pathway maight be involved in the protective effect of SGD agianst PICI Animal experiments displayed that SGD significantly alleviated cognitive impairment induced by paclitaxel, and decreased neuronal apoptosis. Furthermore, SGD remarkably reduced IL-1β, TNF-α and microglia activation, while enhanced SOD activity in hippocampus. In addition, SGD could inhibit NETs formation, evidenced by decreasing the level of plasma MPO-DNA complex, as well as MPO and PAD4 expression. Western blotting assay suggested that SGD attenuated the elevated expression of PI3 K, AKT, p-AKT and PKC-α induced by paclitaxel, whereas decreased PTEN expression. The results of Mendelian randomization analysis further confirm that PTEN is an important therapeutic target for improving cognitive function. Conclusion: Collectively, our preliminary findings indicated that SGD can improve cognitive function of PICI mice. SGD may play a neuroprotective role by inhibiting NETs formation via PTEN/PI3K/AKT signaling pathway. SGD may be a potential alternative therapy for PICI.